The Alterations and Ramifications of Atticus's Beliefs in Harper Lee's To Kill a Mockingbird (1960) and Go Set a Watchman (2015) - BENZIANE, Chahrazad; BOUHAFER ,Assia; GUELLIL ,Assia (Faculty of Letters and Foreign Languages Department of English, 2019)
The current research is conducted on the basis of approaching Harper Lee's character Atticus Finch in both of To Kill a Mockingbird (1960) and Go Set a Watchman (2015) by means of Freud's theory of personality. In order to achieve the previous aim, the entire work is required to be qualitative and adopts the psychoanalytic approach in addition to the analytical and descriptive methods. The research relies on three principal notions namely a demonstration of the theoretical framework which consists of a brief introduction of Sigmund Freud's psychoanalysis, an unpretentious representation of the substantial elements of the theory, a concise description of its significance in terms of literary text analysis, in addition to an overall description of the principles of his theory of personality. Moreover, an analysis of Atticus Finch's actions in the context of To Kill a Mockingbird (1960) is introduced. Similarly to the previous idea but in a different context, an investigation of the protagonist in Go Set a Watchman (2015) is proposed. This procedure of scrutinizing the character results in defining which elements of Freud's theory of personality has an impact on his behaviors. Hence, it leads to detecting the essence of the author’s presence which is demonstrated in the implication of the historical, social and political aspects and their impact on her presentation of Atticus Finch in both novels especially in Go Set a Watchman (2015).